A self-consistent design method of the autothermal dual circulating fluidized bed reactor for in-situ gasification chemical looping combustion of coal - Xi Chen; Haibo Zhao (Carbon Capture Science & Technology)
This paper establishes a design method for the autothermal dual circulating fluidized bed reactor (DCFBR) of the coal-fueled in-situ gasification chemical looping combustion (iG-CLC) process. This method, grounded in a self-consistent phenomenological model, comprehensively elucidates the factors of mass and energy conservation, fuel and oxygen carrier (OC) reaction processes, and fluidization characteristics within the reactor. It is particularly suitable for the rapid screening of numerous potential designs, obtaining detailed design parameters, and studying their interrelationships. Utilizing this method, the regulation patterns of dual-bed interactive transport-reaction phenomena within a 5 MWth iG-CLC DCFBR are studied. Firstly, the effects of key design parameters on the OC circulation rate and bed inventory are analyzed. Following this, the impacts of circulation rate on the interactive heat and mass transfer between two beds are examined, delineating a reasonable range for the control of autothermal CLC process (circulation rate of 50–90 kg/m2s, temperature difference of 30–90 °C, OC conversion of 0.2–0.35, and oxygen-fuel ratio of 3–6). Subsequently, this paper investigates the influences of main design parameters on the performance metrics, such as gas/solid fuel conversion, operational costs, and operational benefits. It is found that the carbon stripper significantly enhances the carbon capture efficiency of the device, provided that its separation efficiency is maintained above 70–95 %. Sensitivity analysis is employed to study the response patterns of performance metrics to changes in input parameters. Ultimately, based on these analyses, a design scheme for the 5 MWth reactor is determined, with a detailed examination of the pressure balance state of the reactor under the design conditions, and the balanced material and energy flows at the reactor inlets and outlets.